ẢNH HƯỞNG CỦA SELEN HỮU CƠ LÊN SINH TRƯỞNG, TỶ LỆ SỐNG, THÀNH PHẦN SINH HÓA VÀ KHẢ NĂNG MIỄN DỊCH CỦA CÁ CHẼM (Lates calcarifer Bloch1790) - Trần, Đức Diễn; Huỳnh, Minh Sang; Lê, Minh Hoàng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE EFFECT OF ORGANIC SELENIUM ON GROWTH, SURVIVAL RATIO BIOCHEMISTRY COMPOSITION AND IMMUNOLOGICAL CAPACITY OF ASIAN SEABASS (Lates calcarifer Bloch 1790)To determine the appropriate content of organic selenium in food which can improve biochemical and immune ability of Asian seabass (Lates calcarifer Bloch 1790), a number of fish fry fed in different diets containing Sel-plex supplement concentrations of 0.0 (control), 0.3, 0.5, 0.7 g/kg respectively for 50 days are studied. The research results show that the organic selenium supplementation of 0.5 g Sel-plex/ kg (5.54 mg Se/ kg) proves to be the most appropriate and can improve growth rate, reduce the moisture in the muscles, increase crude protein content, total blood cells THC and resistance to Vibrio parahaemolyticus density of 106 cfu/ml.